Chemistry an introduction to organic, inorganic and physical chemistry - Housecroft, Catherine E. 1955-; Constable, Edwin C. 1955- (Prentice Hall, an imprint of Pearson Education Limited, 2010)
Chemistry provides a robust coverage of the different branches of chemistry - with unique depth in organic chemistry in an introductory text - helping students to develop a solid understanding of chemical principles, how they interconnect and how they can be applied to our lives
Keywords: Anorganische Chemie; Organische Chemie; Chemie; Physikalische Chemie; Chemistry / Textbooks; Chemistry; Chemistry / Problems, exercises, etc; Lehrbuch